2015
DOI: 10.4238/2015.december.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α and interleukin-6 gene polymorphism association with susceptibility to celiac disease in Italian patients

Abstract: ABSTRACT. The aim of this research was to study polymorphisms in the genes encoding cytokines interleukin-6 (IL-6) and tumor necrosis factoralpha (TNF-α) in patients with celiac disease (CD) antigens DQ2 (DQ2-positive) or DQ8 (DQ8-positive). We compared the results with healthy controls to determine whether any of the polymorphisms have a role in susceptibility to CD. 16343-16352 (2015) included in the study. Analysis of single nucleotide polymorphisms (SNPs) was carried out using the polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Most of the evidences suggest that the endogenous production of TNF-α may be influenced by TNF-α promoter polymorphisms, thereby affecting messenger RNA (mRNA) and protein expression levels26. In view of facts about the significant role of TNF-α gene in modulation of acute inflammation and host innate immunity, various studies have been conducted to analyze the relationship between TNF-α -308 G > A gene polymorphism and the development of CD, but the results from different published studies were contradictory and inconclusive1415161718192021222324. In order to improve the statistical power, we performed the present meta-analysis to assess the said association of TNF-α -308 G > A polymorphism and CD risk from eleven case-control studies, as combining of the data from different studies has an advantage of reducing the random error27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the evidences suggest that the endogenous production of TNF-α may be influenced by TNF-α promoter polymorphisms, thereby affecting messenger RNA (mRNA) and protein expression levels26. In view of facts about the significant role of TNF-α gene in modulation of acute inflammation and host innate immunity, various studies have been conducted to analyze the relationship between TNF-α -308 G > A gene polymorphism and the development of CD, but the results from different published studies were contradictory and inconclusive1415161718192021222324. In order to improve the statistical power, we performed the present meta-analysis to assess the said association of TNF-α -308 G > A polymorphism and CD risk from eleven case-control studies, as combining of the data from different studies has an advantage of reducing the random error27.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping aforesaid information in view, to date a number of case control and cohort studies have been performed to investigate the association of TNF-α -308 G > A gene polymorphism and CD susceptibility1415161718192021222324. However, the results are inconsistent and controversial because of small sample size of individual study and possible selective bias.…”
mentioning
confidence: 99%
“…Dema et al (7) determined that IL-6 (-174G/C) polymorphism increased the risk of CD in girls. However, another study determined no relation between this polymorphism and CD (2). IL-6 (-572G/C) (rs1800796) is found adjacent to the IL-6 5' promoter region (8).…”
mentioning
confidence: 99%
“…Genetic polymorphisms have been reported to contribute to CD sensitivity by altering the levels and functions of cytokines (2). This study aimed to evaluate IL-6 (-572G/C) (rs1800796) and IL-17 (-197A/G) (rs2275913) gene polymorphisms in children with CD.…”
mentioning
confidence: 99%
“…The IL-6 gene, located at chromosome 7p21-24, is composed of 4 introns and 5 exons. Since single nucleotide polymorphisms of IL-6 gene promoter may affect the expression and secretion of IL-6, and subsequently the altered circulating levels might result in relevant biological responses, and the IL-6 polymorphism has been regarded as a crucial modulator in pathogenesis of various diseases, including Alzheimer's disease, type 2 diabetes, celiac disease, chronic obstructive pulmonary disease and osteoarthritis (de Albuquerque Maranhão et al, 2015;Fernandes et al, 2015;Xie et al, 2015;Buraczynska et al, 2016;Ramos Dos Santos et al, 2016). Although several studies have shown that IL-6 polymorphisms could be also involved in the development of CAD, the conclusions were not consistent Liu et al, 2015;Wang et al, 2015;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%